Rock Slope Stability at Bukit Permata, Lumut, Perak - Mohd Naguib, Muhammad Naqiuddin (2016)
Slope failure is the common geohazard which occurs throughout Malaysia. Its occurrence mostly related to heavy rainfalls which amplify the grade of weathering within the rock, the sediment stability, and the weak rock structure itself where there are a lot of fracturing ad opening which invites the weathering agents deep within a slope structure. Other factors in which slope failure occur in artificial slope might be due to a poor road construction planning and design where the slopes were exposed in a critical exposure to weathering and were designed in a very unstable structure.